Maternal and Newborn Health Service in Federal System of Nepal - Bhattarai Gautam, Saraswoti Kumari (Journal of Nursing Education of Nepal, 2022)
Maternal health is the health status of women during pregnancy, childbirth, and the post-partum period, which combines the health care dimension of family planning, preconception, prenatal care and postnatal care is vital to reduce maternal and newborn morbidity and mortality. In this regard, government of Nepal is adopted two key strategies to improve maternal health: ensuring that a selected health facilities have emergency obstetric care services that are available 24 hours a day and the presence of health personnel with midwifery skills who can competently provide safe and effective delivery care. In this context, three level of government namely; federal, provincial and local government is providing the maternal and neonatal health service. Keywords: Levels of Care, Maternal health, Skilled Health Professionals, Service Sites
Keywords: Levels of Care; Maternal health; killed Health Professionals; Service Sites